دور أسلوب التكلفة على أساس الأنشطة في تخ - ميلود, تومي; نعيمة, زعرور (Recherches économiques et managériales; Vol. 14 (2013): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES (DÉCEMBRE))
تشهد بيئة الأعمال تغيرات كبيرة صناعية وتكنولوجية خاصة في محيط تنافسي، ونجد أن المؤسسات تسعي في مثل هذه الظروف إلي التركيز على اتخاذ القرارات الملائمة لتحقيق الأهداف المخطط لها وتلبية حاجات أفراد المجتمع، والبحث عن التفوق بتعزيز قدرتها التنافسية في كافة المجالات. وبسبب الانتقادات التي وجهت للأساليب التقليدية لمحاسبة التكاليف بسبب مشكلة تخصيص التكاليف الغير مباشرة، ظهر أسلوب التكلفة على أساس الأنشطة (ABC)، إلا أننا سنحاول في مقالنا هذا تسليط الضوء على أسلوب التكلفة على أساس الأنشطة كأسلوب لتخفيض التكاليف. Résumé : Witnessing the business environment changes large industrial and technologique especially in a competitive environment, and we find that institutions are seeking in such circumstances to focus on making appropriate decisions to achieve the planned objectives and meet the needs of members of the community, and the search for excellence by strengthening its competitiveness in all areas. Because of the criticism directed at the traditional methods of cost accounting because of the problème of the allocation of indirect costs, the back of cost méthode on the basis of activités (ABC), but we will try our article in this shed light on the cost méthode on the basis of the activités as a way to reduce costs .